RETRACTION NOTICE TO: Dampak Pembangunan di Era Globalisasi terhadap Perwujudan Hak Asasi Manusia di Lingkungan yang Baik dan Sehat - Okta Zeruya Samdra Pandapotan Nainggolan (Jurnal Hukum Lex Generalis, 2023)
The manuscript entitled "The Impact Of Development In The Era Of Globalization On The Realization Of Human Rights In A Good And Healthy Environment" published in Lex Generalis Law Journal Vol.3 No.12 (December 2022) on the link https://ojs.rewangrencang.com/index.php/JHLG/article/view/317 to the Editor's search has the main similarity substance with the manuscript that has been published previously in another journal, namely Jurnal Pembangunan Hukum Vol.1 No.3 (2014) on the http://jurnal.unissula.ac.id/index.php/PH/article/view/1487/1155. When we came across these findings, we tried to contact the authors via email (as they did not contact us via text message or an app like WhatsApp nor did we find their personal social media accounts). However, because there is no answer to explain this problem, we here unilaterally see that there is copyright infringement or plagiarism by copying and pasting the entire file in one of the manuscripts in the Jurnal Pembangunan Hukum (author: Setyo Utomo), making slight changes such as changing the word "Influence" to "Impact", and submitting the file to our journal via OJS. Thus taking into account the absence of evidence or rebuttal from the author, the Editorial decided to retract this manuscript from our journal.